Customer Based Retailer Equity of Apparel Retail Stores - S., Deepa; Chitramani, P. (Indian Journal of Marketing, 2016)
The present competitive retail environment demands the rise of the retailer as a brand and its brand equity as of importance. The research gap of mediating nature of associations and perceived quality and their role in converting the customers from the awareness stage to loyalty was the focus of this research. Customer based retailer equity is conceptualized as a multi-dimensional construct comprising of : retailer awareness, retailer associations, retailer perceived quality, and retailer loyalty. A questionnaire based survey was conducted among the female customers of the major apparel retail stores in Coimbatore. The empirical analysis revealed that there is a positive correlation among the four dimensions of retailer equity. The hierarchical regression analysis was carried out by meeting the four requirements of Baron and Kenny (1986) for the mediator variables. Retailer association and retailer perceived quality were found to be acting as mediators between retailer awareness and retailer loyalty relationship, as the effect of retailer awareness was found to be remarkably lower and became non significant in the final model. This research paper highlighted three important theoretical contributions to retailer equity. First, the paper empirically tested the retailer equity model in the Indian retail context. Second, it explained the interrelationships among the four dimensions of retailer equity. Third, the paper attempted to fill in the gap of retailer equity research by demonstrating the existence of potential causal order of relationships among retailer equity dimensions as in the brand equity literature. The conceptual and practical outcome of the empirical results is that the four dimensions can be bundled together as marketing strategies. Strong retail brand awareness will help the retailers to attract customers into the store for the first time. However, a customer is converted into a loyal customer based upon the strength of favorable associations created by the retailers and by meeting the customers' quality expectations.